Synthesis and Functionalization of Isomeric Sesquihomodiamantenes - Fokin, Andrey; Justus Liebig University Giessen (My University, 2023)
Anti- and syn-sesquihomodiamantenes (SDs) were prepared and structurally characterized. Anti-SD and parent sesquihomoadamantene (SA) were CH-bond functionalized utilizing a phase-transfer protocol. The DFT computed ionization potentials of unsaturated diamondoid dimers correlate well with the experimental oxidation potentials obtained from cyclic voltammetry. Similar geometries ensue for both the reduced and ionized SD states, whose persistence is supported by β-hydrogen’s spatial sheltering. This makes SDs promising building blocks for the construction of diamond materials with high stability and carrier mobility. We provide free induction decay (FID) of nuclear magnetic resonance (NMR) spectra of new compounds obtained within the manuscript accepted for publication in Journal of the Organic Chemistry (American Chemical Society). The NMR spectra were recorded in CDCl3 solutions on a Bruker AV 400 (400 MHz for 1H NMR and 100 MHz for 13C NMR), Bruker AV 600 (600 MHz for 1H NMR and 125 MHz for 13C NMR), Bruker Avance Neo (700 MHz for 1H NMR and 176 MHz for 13C NMR), and Bruker AV 850 (850 MHz for 1H NMR and 214 MHz for 13C NMR) spectrometers at 298 K. To open and read the FID files either use the programs "Mnova" (https://mestrelab.com/download/mnova/) or "Bruker TopSpin" (https://www.bruker.com/en/products-and-solutions/mr/nmr-software/topspin.html).
Keywords: C–H-bond functionalization, diamondoids, hydrocarbon radical anions, ionization potentials, nanodiamond, paramagnetic states, sp2-defects.; ddc:540